Neuroticism and Individual Differences in Neural Function in Unmedicated Major Depression: Findings from the EMBARC Study - Fournier, Jay C. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2016)
BACKGROUND: Personality dysfunction represents one of the only predictors of differential response between active treatments for depression to have replicated. In this study, we examine whether depressed patients with higher neuroticism scores, a marker of personality dysfunction, show differences versus depressed patients with lower scores in the functioning of two brain regions associated with treatment response, the anterior cingulate and anterior insula cortices. METHODS: Functional magnetic resonance imaging data during an emotional Stroop task were collected from 135 adults diagnosed with major depressive disorder at four academic medical centers participating in the Establishing Moderators and Biosignatures of Antidepressant Response for Clinical Care (EMBARC) study. Secondary analyses were conducted including a sample of 28 healthy individuals. RESULTS: In whole-brain analyses, higher neuroticism among depressed adults was associated with increased activity in and connectivity with the right anterior insula cortex to incongruent compared to congruent emotional stimuli (ks>281, ps<0.05 FWE corrected), covarying for concurrent psychiatric distress. We also observed an unanticipated relationship between neuroticism and reduced activity in the precuneus (k=269, p<0.05 FWE corrected). Exploratory analyses including healthy individuals suggested that associations between neuroticism and brain function may be nonlinear over the full range of neuroticism scores. CONCLUSIONS: This study provides convergent evidence for the importance of the right anterior insula cortex as a brain-based marker of clinically meaningful individual differences in neuroticism among adults with depression. This is a critical next step in linking personality dysfunction, a replicated clinical predictor of differential antidepressant treatment response, with differences in underlying brain function.